Rules of thumb for chemical engineers - Hall, Stephen (Butterworth-Heinemann, 2012)
The most complete guide of its kind, this is the favored handbook for chemical and process engineers who need a reliable and authoritative solution to their practical on the job problems. Includes all new material on new processing sectors, include biopharmaceuticals. The text is comprehensively revised and updated with new data and formulas. Rules of Thumb for Chemical Engineers solves process design problems quickly, accurately and safely, with hundreds of common sense techniques, shortcuts and calculations. Key features; Rules of Thumb for Chemical Engineers brings together solutions, information and work-arounds that engineers in the process industry need to get their job done. New material in the Fifth Edition includes physical properties for proprietary materials, six new chapters, including pharmaceutical, biopharmaceutical sector heuristics, process design with simulation software, and guidelines for hazardous materials and processes.-Now includes SI units throughout alongside imperial, and now accompanied by online calculation tools New to this edition; New chapter on biopharmaceutical systems New chapter on closed-loop heat transfer systems Extensively rewritten chapters on fluid flow, fractionation, heat exchangers, pumps, compressors, safety, and controls. Latest information on packed columns and structured packings Excel workbooks, with Visual Basic for Applications function subroutines, that solve many of the problems in the book. Fully updated references Rules of Thumb for Chemical Engineers brings together solutions, information and work-arounds that engineers in the process industry need to get their job done.-New material in the Fifth Edition includes physical properties for proprietary materials, six new chapters, including pharmaceutical, biopharmaceutical sector heuristics, process design with simulation software, and guidelines for hazardous materials and processes Now includes SI units throughout alongside imperial, and now accompanied by online calculation tools and a searchable Rules of Thumb library.
Keywords: Chemical engineering -- Handbooks, manuals, etc.; elektronické knihy; electronic books